Self-Rated Competence of Ugandan Healthcare Workers to Obtain Informed Consent for Autopsy - Bongomin, Felix; Kibone, Winnie; Nantale, Ritah; Lukande, Robert; Bromley, Ruth; Muzoora, Conrad; Hamer, Davidson H. (The American journal of tropical medicine and hygiene, 2024)
We examined the self-rated competence of Ugandan healthcare workers (HCWs) in obtaining informed consent for autopsies, considering the challenges of low autopsy acceptance rates globally. In September and October 2023, we conducted a nationwide cross-sectional study of HCWs, who provided informed consent to participate and completed an online, self-administered questionnaire. Participants’ self-rated competence in obtaining informed consent for autopsy was assessed through Likert scale questions. Knowledge and practices were also assessed. All scores were converted to percentages, with scores $80% indicating higher competence. We enrolled 216 HCWs (including 145 [67.1%] doctors), with a mean age of 31.6 6 7.2 years. Overall, 55.6% (n 5 120) had ever assisted in obtaining consent for autopsy, 43.6% (n 5 100) had ever obtained consent for autopsy themselves, and 13.4% (n 5 29) had ever attended training on obtaining consent for autopsy. The mean competency score was 59.8 6 17.0% (perfect score,100%), with 29(13.4%) participants demonstrating high competence. Healthcare workers with adequate knowledge had higher competence scores (odds ratio [OR]: 15.0, 95% CI: 6.17–36.58, P ,0.001). Compared with nurses/midwives, doctors had 73% lower odds of having a high competence score (adjusted OR:0.27,95% CI:0.08–0.94, P 5 0.040). Fewer than one in ﬁve Ugandan HCWs demonstrated high self-rated competence or possessed adequate knowledge regarding informed consent for autopsies, and only a few had received specialized training on how to obtain consent for an autopsy. Therefore, there is a pressing need for enhanced training and increased awareness among Ugandan HCWs in obtaining informed consent for autopsies.
Keywords: Postmortem autopsy; Healthcare Workers; Informed Consent